Exploration of the Need for the Development of PjBL-Based Interactive E-LKPD to Strengthen the Attitude of Unity and Critical Thinking of Elementary School Students - Siti Latifah; Osa Juarsa; Eko Risdianto; Endang Widi Winarni (Journal of Primary Education (JPE), 2026)
Strengthening the attitude of unity and critical thinking skills in elementary school students is an important demand in 21st century learning, but in the implementation in the classroom there are still obstacles in the use of interactive learning media that supports the project-based learning (PjBL) approach. This research aims to explore the needs of teachers and students for the development of PjBL-based interactive E-LKPD as an effort to strengthen the attitude of unity and critical thinking skills of elementary school students. This study uses a qualitative approach with an exploratory study design. The research subjects include teachers and elementary school students who are selected purposively. Data was collected through in-depth interviews, learning observations, and documentation. Furthermore, it was analysed using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that teachers are still experiencing limitations in developing interactive and contextual learning media. Meanwhile, students show the need for media that is interesting, easy to use, and able to relate learning to real life. In addition, the PjBL approach has the potential to develop a collaborative attitude as part of the attitude of unity and increase students' critical thinking, but it has not been supported by optimal learning tools such as interactive E-LKPD assisted by digital platforms.  This research emphasizes the importance of developing an interactive E-LKPD based on PjBL that is in accordance with the needs of teachers and students. These findings provide a strong basis for developmental research in order to improve the quality of learning in primary schools, especially in strengthening unity and critical thinking skills.